Case Report: Abnormalities of sperm motility and morphology in a patient with Leber hereditary optic neuropathy: Improvement after idebenone therapy - Orssaud, Christophe; Barraud Lange, Virginie; Wolf, Jean Philippe; LeFoll, Nathalie; Soufir, Jean Claude (Frontiers in Neurology, 2023)
Background : We report the improvement of semen characteristics of a male patient with a Leber hereditary optic neuropathy after administration of idebenone. This molecule can by-pass the complex -I and stimulate complex-II function. Case: A male patient developed a Leber hereditary optic neuropathy when he was 18. At the age of 30 years-old, he presented with an infertility lasting for 2 years. Semen analyses showed low motility spermatozoa and a high percentage of morphological or ultrastructural abnormalities. Levels of epididymal markers were strongly atypical. A varicocele was embolized without major effect of sperm quality six months later. Idebenone was then prescribed in order to improve his visual acuity. After five months of this treatment, motility of spermatozoa increased, and their vitality improved. Conclusion: This is the first description of improvement of semen analysis after idebenone administration in a patient with Leber hereditary optic neuropathy. This case also draws attention to sperm pathologies in patients with mitochondrial disorders. It is the first report of anomaly of spermatozoas in a patient harboring a mitochondrial mutation. It is possible that the presence of a varicocele favored this infertility by aggravating epidymal oxidative stress and increasing the negative effects of the mtDNA mutation.